Alcohoi Content of Traditional Brews and Miti ni Dawa in Kenya (The East and Central African Journal of Pharmaceutical Sciences, 2020)
A number of alcoholic preparations sold in Kenya were analysed for their alcohol content. The alcohol content for various samples varied over a wide range. In the legal beers it ranged between 3.8 to 7.4% volume parts. Busaa had an alcohol content between 2 and 7.5 for Muratina it was 2.1 - 9 %, Miti ni Dawa 1.2 - 8.4 % and Changaa 16.2 - 31.5%. A sample of Miti ni dawa and changaa were found to contain trace amounts of methanol possibly a result of hydrolysis of methoxy groups in pectins. Fermentation temperature was found to be an important determinant of the final alcoholic content in Miti ni Dawa.
Keywords: Kenya, traditional, other brews, alcohol content